2017
DOI: 10.4186/ej.2017.21.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Asbestos Cement Water Pipe Aging and Pipe Prioritization Using Monte Carlo Simulation

Abstract: For buried Asbestos cement (AC) pipes in service, internal and external surface degradation occur by dissolution or leaching of cement-based components leading to loss of pipe strength. Since water quality and soil environment cannot be completely specified along a pipeline, a management methodology for AC water pipelines is required to estimate the probability of pipe failure as ageing proceeds. The paper describes the technique and its application to experimental data, which illustrates in three parts. First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Two main types of concrete corrosion occur in AC pipes: 1) lime leaching and 2) sulphate attack (Hu et al, 2013). Early AC pipes were manufactured using free lime, which was susceptible to lime leaching in certain soil conditions, being particularly evident when silica was not used (Punurai and Davis, 2017). Lime leaching occurs when external pipe conditions are acidic with a low ion content mobile water source (typically a high groundwater level) (Hu et al, 2013;Silva et al, 2002).…”
Section: Corrosion and Chemical Degradationmentioning
confidence: 99%
“…Two main types of concrete corrosion occur in AC pipes: 1) lime leaching and 2) sulphate attack (Hu et al, 2013). Early AC pipes were manufactured using free lime, which was susceptible to lime leaching in certain soil conditions, being particularly evident when silica was not used (Punurai and Davis, 2017). Lime leaching occurs when external pipe conditions are acidic with a low ion content mobile water source (typically a high groundwater level) (Hu et al, 2013;Silva et al, 2002).…”
Section: Corrosion and Chemical Degradationmentioning
confidence: 99%
“…3 allows the Weibull scale and shape parameters to be estimated and reported together with strength loss rate values. Following the procedure outlined in [27], the scale and shape parameters for different pipe sizes were calculated and shown in Table 4. Fig.…”
Section: Probability Distribution Of Degradation In Ac Water Pipesmentioning
confidence: 99%
“…In previous work, it was determined that X-ray computed tomography may indeed provide a detailed description of AC pipe degradation [15]. In that work, it was also revealed that the leaching of AC drinking water pipes occurs in a far less homogeneous way than is traditionally assumed [16][17][18].…”
Section: Introductionmentioning
confidence: 99%